INDICATIVE PLANNING: DEFINITION AND RUSSIAN PRACTICE - Elena V. Ustyuzhanina; Sergey G. Evsyukov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article considers possibilities of using indicative planning to modernize Russian economy. Topicality of the subject is connected with problems facing our country in conditions of changing price proportions and altering international chains of cooperation. The authors came to the conclusion that indicative planning implies three different approaches to planning and economy management: information-oriented, organizational and program-targeted. By analyzing the practice of budget programming existing in our country they draw a conclusion that program-targeted approach to planning has serious drawbacks exacerbated by subjective errors in its use. In authors' point of view the most suitable for our country approach is organizational which combines well-balanced economic planning and the system of state regulation of economy.